Correction: five-year predictors of physical activity decline among adults in low-income communities: a prospective study - Platt Robert W; O'Loughlin Jennifer L; Weiss Deborah R; Paradis Gilles (BMC, 2007)
Abstract After publication it was brought to our attention that the information for one of the variables in Table <tblr tid="T1">1</tblr> was incorrect (Weiss, O'Loughlin et al. International Journal of Behavioral Nutrition and Physical Activity 2007, 4:2). The variable in question is "Use of a neighborhood facility for activity". In the first column, the first row should read "yes", and the second row, "no". In the second column, the first row should read 25.8 (41) and the second row, 41.3 (152). <tbl id="T1"> Table 1 Unadjusted and adjusted Odds Ratios for potential predictors of becoming inactive [1]. <tblbdy cols="4"> <r> <c ca="left"> Potential predictor </c> <c ca="left"> Participants who became inactive </c> <c ca="left"> Unadjusted OR (95% CI) </c> <c ca="left"> Adjusted OR (95% CI) </c> </r> <r> <c cspan="4"> </c> </r> <r> <c ca="left"> Sex, % (n) </c> <c> </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> Male </c> <c ca="left"> 31.1 (77) </c> <c ca="left"> 1.00 (Ref.) </c> <c ca="left"> 1.00 (Ref.) </c> </r> <r> <c indent="1" ca="left"> Female </c> <c ca="left"> 41.6 (116) </c> <c ca="left"> 1.58 (1.10, 2.27) </c> <c ca="left"> 1.63 (1.09, 2.43) </c> </r> <r> <c ca="left"> Age (years), mean (SD) </c> <c ca="left"> 39.5 (12.2) </c> <c ca="left"> 1.03 (1.01, 1.05) </c> <c ca="left"> 1.02 (1.01, 1.04) </c> </r> <r> <c ca="left"> Self-rated health, % (n) </c> <c> </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> Excellent </c> <c ca="left"> 29.8 (50) </c> <c ca="left"> 1.70 (1.35, 2.16) </c> <c ca="left"> 1.39 (1.05, 1.84) </c> </r> <r> <c indent="1" ca="left"> Good </c> <c ca="left"> 32.6 (84) </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> Average </c> <c ca="left"> 57.8 (48) </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> Poor/Very poor </c> <c ca="left"> 64.7 (11) </c> <c> </c> <c> </c> </r> <r> <c ca="left"> BMIa, % (n) </c> <c> </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> <25 </c> <c ca="left"> 32.1 (117) </c> <c ca="left"> 1.00 (Ref.) </c> <c ca="left"> 1.00 (Ref.) </c> </r> <r> <c indent="1" ca="left"> =25 </c> <c ca="left"> 46.6 (76) </c> <c ca="left"> 1.84 (1.26, 2.69) </c> <c ca="left"> 1.57 (1.03, 2.40) </c> </r> <r> <c ca="left"> Smoking status, % (n) </c> <c> </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> Current smoker </c> <c ca="left"> 37.5 (77) </c> <c ca="left"> 1.00 (Ref.) </c> <c ca="left"> 1.00 (Ref.) </c> </r> <r> <c indent="1" ca="left"> Past/Never smoker </c> <c ca="left"> 36.2 (121) </c> <c ca="left"> 1.06 (0.73, 1.53) </c> <c ca="left"> 0.98 (0.78, 1.23) </c> </r> <r> <c ca="left"> Income, % (n) </c> <c> </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> <20,000 </c> <c ca="left"> 39.5 (68) </c> <c ca="left"> 0.82 (0.65, 1.03) </c> <c ca="left"> 0.95 (0.73, 1.24) </c> </r> <r> <c indent="1" ca="left"> 20,000-40,000 </c> <c ca="left"> 35.8 (62) </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> 40,000+ </c> <c ca="left"> 30.2 (42) </c> <c> </c> <c> </c> </r> <r> <c ca="left"> Self-efficacy score, mean (SD) </c> <c ca="left"> 2.2 (0.6) </c> <c ca="left"> 1.61 (1.20, 2.26) </c> <c ca="left"> 1.46 (1.00, 2.14) </c> </r> <r> <c ca="left"> Use of a neighborhood facility for activity, % (n) </c> <c> </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> Yes </c> <c ca="left"> 25.8 (41) </c> <c ca="left"> 1.00 (Ref.) </c> <c ca="left"> 1.00 (Ref.) </c> </r> <r> <c indent="1" ca="left"> No </c> <c ca="left"> 41.3 (152) </c> <c ca="left"> 2.03 (1.34, 3.06) </c> <c ca="left"> 1.61 (1.02, 2.55) </c> </r> <r> <c ca="left"> Education, % (n) </c> <c> </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> Elementary/some secondary </c> <c ca="left"> 52.6 (50) </c> <c ca="left"> 0.74 (0.63, 0.86) </c> <c ca="left"> N/A* </c> </r> <r> <c indent="1" ca="left"> Completed secondary/some college </c> <c ca="left"> 40.2 (47) </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> Completed college </c> <c ca="left"> 32.5 (27) </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> Some post-secondary </c> <c ca="left"> 29.8 (67) </c> <c> </c> <c> </c> </r> <r> <c ca="left"> Receives encouragement for activity, % (n) </c> <c> </c> <c> </c> <c> </c> </r> <r> <c indent="1" ca="left"> No </c> <c ca="left"> 35.2 (113) </c> <c ca="left"> 1.00 (Ref.) </c> <c ca="left"> N/A* </c> </r> <r> <c indent="1" ca="left"> Yes </c> <c ca="left"> 38.5 (79) </c> <c ca="left"> 0.87 (0.60, 1.25) </c> <c> </c> </r> </tblbdy> <tblfn> aBody Mass Index * Not included in final model </tblfn> </tbl>